FORECASTING TAX REVENUES TO THE BUDGET AS A FACTOR IN THE EFFECTIVE MANAGEMENT OF PUBLIC FINANCE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Forecasting and planning tax and levy receipts is one of the most effective management functions of the state in a market economy. Forecasting and planning issues are important in connection with the need to improve the tax process.